2021
DOI: 10.3389/fendo.2020.542942
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Hermaphroditic Stage in Early Male Gonadal Development in Little Yellow Croaker, Larimichthys polyactis

Abstract: Animal taxa show remarkable variability in sexual reproduction, where separate sexes, or gonochorism, is thought to have evolved from hermaphroditism for most cases. Hermaphroditism accounts for 5% in animals, and sequential hermaphroditism has been found in teleost. In this study, we characterized a novel form of the transient hermaphroditic stage in little yellow croaker (Larimichthys polyactis) during early gonadal development. The ovary and testis were indistinguishable from 7 to 40 days post-hatching (dph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Finding a transitional species in the evolution of hermaphroditism and gonochorism in Perciformes is very important for the study of the evolution of the fish reproductive spectrum. Our previous study demonstrated that L. polyactis ' unique pattern of testis differentiation is neither typical hermaphroditism nor gonochorism (Xie et al, 2021). We speculate that this gonadal differentiation pattern inL.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Finding a transitional species in the evolution of hermaphroditism and gonochorism in Perciformes is very important for the study of the evolution of the fish reproductive spectrum. Our previous study demonstrated that L. polyactis ' unique pattern of testis differentiation is neither typical hermaphroditism nor gonochorism (Xie et al, 2021). We speculate that this gonadal differentiation pattern inL.…”
Section: Discussionmentioning
confidence: 76%
“…Little yellow croaker (L . polyactis ) was found to be a good model for investigating the direction of evolution of hermaphroditism and gonochorism due to its special sexual reproduction process, in which males undergo a male-specific transient hermaphroditic stage (Xie et al, 2021). Briefly, L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larimichthys polyactis can reach sexual maturity after 1 year (Lim et al, 2010;Xie et al, 2021), and fish of the S1 and S2 groups were believed to be in the spawning period. Therefore, the otoliths of the S1 group were analysed for the chemical composition of the core and the first annual ring (Y1) reflecting the local environment of the natal site and the first spawning site, respectively, and those of the S2 and O2 groups were in addition analysed for the composition of the second annual ring (Y2).…”
Section: Otolith Elemental Analysismentioning
confidence: 99%
“…Small yellow croaker (Larimichthys polyactis) is an important commercial fish species endemic to the Northwest Pacific, particularly coastal waters of the East China, Yellow, and Bohai Sea between China and the Korean Peninsula (Lin, 1987). L. polyactis is an iteroparous species, which starts spawning at the age of 1 year, as evidenced by histological analyses of female individuals (Xie et al, 2021). For decades, L. polyactis has been an important source of seafood for local markets in China, Japan, and South Korea (Ma et al, 2020;Szuwalski et al, 2020); however, environmental deterioration and overfishing have led to a major decline in its population since the 1970s (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%